Study of GaN Hall Effect Magnetic Sensors - Vlad Marsic; Soroush Faramehr; Isha Maini; David A. J. Moran; Petar Igic (IEEE Access)
The GaN Hall sensors are the latest advancements in non-intrusive active monitoring, designed to be integrated on GaN power transistors to enable in-situ condition monitoring, hence boosting device reliability and life. This paper describes step-by-step the basic procedures required for the fabrication of a three-terminal Hall-effect sensor on GaN, challenges and a robust testing method that can deliver consistent results when testing under diverse laboratory external hazards. This work is presenting the first three-terminal current sensing GaN Hall sensor reported in literature, which have been tested at room temperature under various magnetic field intensities and polarities in order to determine its sensitivity. Since even when properly using the most suitable scientific equipment, errors may occur from insufficient information regarding the relative angle between the magnetic field and the active area of the sensor or, data records affected by imperceptible equipment vibrations, this work provides a practical solution on how to detect and mitigate these shortcomings: magnetic quasi-static sources alternatives are discussed and transient recordings of different intensities and polarities of the magnetic field are separated and interpreted similar with the spectrometry diagrams. This comprehensive presented study delivers a consistent testing framework for the new emerging generation of magnetic sensors.